Early mortality after late initiation of antiretroviral therapy in the TREAT Asia HIV Observational Database of IeDEA Asia-Pacific - Rupasinghe, Dhanushi (HIV Med, 2019)
BACKGROUND: Early mortality among those still initiating ART with advanced stages of HIV infection in resource-limited settings remains high despite recommendations for universal HIV treatment. We investigated risk factors associated with early mortality in PLHIV starting ART at low CD4 levels in the Asia-Pacific. METHODS: PLHIV enrolled in TAHOD who initiated ART with CD4 <100 cells/μL between 2003 – 2018 were included. Early mortality was defined as death within one year of ART initiation. PLHIV in follow-up for more than one year were censored at 12 months. Competing risk regression was used to analyse risk factors with those lost-to follow-up as a competing risk. RESULTS: 1813 PLHIV were included, of which 74% were males. With 73 (4%) deaths, the overall first year mortality rate was 4.27 per 100 person-years (/100PYS). 38 (52%) of deaths were AIDS-related, 10 (14%) IRIS-related, 13 (18%) non-AIDS-related and 12 (16%) unknown. Risk factors included having BMI <18.5 (SHR 2.91, 95% CI 1.60-5.32) compared to BMI 18.5 – 24.9, and alanine aminotransferase (ALT) ≥5 times its upper limit of normal (ULN) (SHR 6.14, 95% CI 1.62-23.20) compared to ALT <5 times its ULN. Higher CD4 (51-100 cells/μL: SHR 0.28, 95% CI 0.14-0.55; and >100 cells/μL: SHR 0.12, 95% CI 0.05-0.26) were associated with reduced hazard for mortality compared to CD4 ≤25 cells/μL. CONCLUSION: 52% of early deaths were AIDS-related. Efforts to initiate ART at CD4 above 50 cell/μl is associated with improved short-term survival rates, even in those with late stages of HIV disease.